PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN SILPA TERHADAP BELANJA MODAL DAN DAMPAKNYA KEPADA PERTUMBUHAN EKONOMI PEMERINTAH DAERAH KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Dessyana Lourine Talluta; Rossy Lambelanova; Ella Wargadinata (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2018)
This study aims to examine the effect of PAD, Balancing Funds in this case Revenue Sharing Fund (DBH), GeneralAllocation Grant (DAU), Special Allocation Fund (DAK), and Budget Financing Surplus (SILPA) on Capital Expenditures and the impact on the Economic Growth of the Regional Government of Kupang City, East Nusa Tenggara Province.This research used mixed methods, with sequential explanatory models, where data collection and quantitative analysis were carried out in the first stage by using secondary data. Population in this research are Statement of Budget Realization and Gross Domestic Regional Product Report by Kupang City Government with 13 years samples from 2005 to 2017. Then followed by collection and analysis of qualitative data in the second stage through interviews, in order to strengthen the results of quantitative research conducted in the first phase. To test and prove the research hypothesis, the analytical method used to test the effect of PAD, DBH, DAU, DAK, and SILPA on Capital Expenditure is Multiple Linear Regression and to examine the Impact of Capital Expenditures on Economic Growth, Simple Linear Regression is used.Based on the results of data analysis it can be concluded that through t test, partially PAD variable gives significant influence towards capital expenditure, it is showed by significant influence in amount of0.001 < 0,05 probability value. DAU gives significant influence towards capital expenditure, it is showed by significant influence in amount of 0.021 < 0.05 probability value. While DBH has no significant effect on Capital Expenditures with significant value of 0.381 > 0.05 probability value. DAK has no significant effect on Capital Expenditures with significant value of 0.219 > 0.05 probability value. SILPA has no significant effect on Capital Expenditures with sig value of 0.305> 0.05 probability value. While through the F Test PAD, DBH, DAU, DAK, and SILPA simultaneously gives significant influence towards capital expenditure with a value of sig 0,000 <0,05 probability value. Furthermore, through t Test Capital Expenditures gives significant influence towards Economic Growth of Kupang city with significant value of 0.010 <0.05 probability value. Key words: Local Own Sources Revenue, Revenue Sharing Fund, General Allocation Grant, Special Allocation Fund, Budget Financing Surplus, Capital Expenditure and Economic GrowthThis study aims to examine the effect of PAD, Balancing Funds in this case Revenue Sharing Fund (DBH), GeneralAllocation Grant (DAU), Special Allocation Fund (DAK), and Budget Financing Surplus (SILPA) on Capital Expenditures and the impact on the Economic Growth of the Regional Government of Kupang City, East Nusa Tenggara Province.This research used mixed methods, with sequential explanatory models, where data collection and quantitative analysis were carried out in the first stage by using secondary data. Population in this research are Statement of Budget Realization and Gross Domestic Regional Product Report by Kupang City Government with 13 years samples from 2005 to 2017. Then followed by collection and analysis of qualitative data in the second stage through interviews, in order to strengthen the results of quantitative research conducted in the first phase. To test and prove the research hypothesis, the analytical method used to test the effect of PAD, DBH, DAU, DAK, and SILPA on Capital Expenditure is Multiple Linear Regression and to examine the Impact of Capital Expenditures on Economic Growth, Simple Linear Regression is used.Based on the results of data analysis it can be concluded that through t test, partially PAD variable gives significant influence towards capital expenditure, it is showed by significant influence in amount of0.001 < 0,05 probability value. DAU gives significant influence towards capital expenditure, it is showed by significant influence in amount of 0.021 < 0.05 probability value. While DBH has no significant effect on Capital Expenditures with significant value of 0.381 > 0.05 probability value. DAK has no significant effect on Capital Expenditures with significant value of 0.219 > 0.05 probability value. SILPA has no significant effect on Capital Expenditures with sig value of 0.305> 0.05 probability value. While through the F Test PAD, DBH, DAU, DAK, and SILPA simultaneously gives significant influence towards capital expenditure with a value of sig 0,000 <0,05 probability value. Furthermore, through t Test Capital Expenditures gives significant influence towards Economic Growth of Kupang city with significant value of 0.010 <0.05 probability value. Key words: Local Own Sources Revenue, Revenue Sharing Fund, General Allocation Grant, Special Allocation Fund, Budget Financing Surplus, Capital Expenditure and Economic Growth <w:LsdException Loc